Application, mechanism and prospects of Fe-based/ Fe-biochar catalysts in heterogenous ozonation process: A review. (April 2023) - Wang, Jingjing; Yuan, Shijie; Dai, Xiaohu; Dong, Bin
Abstract: A growing number of novel organic contaminants have escalated the demands and challenges for water treatment technology. Advanced oxidation processes based on ozone have the advantage of strong oxidative capacity and higher efficiency, which have promising application prospects in the treatment of refractory organic contaminants. Biochar has attracted a lot of interest in recent years in wastewater treatment owing to its porous structure, portable preparation and outstanding stability. Moreover, iron species are widely used in catalytic ozonation owing to their magnetic polarization, vast abundance and low price. Despite a plethora of research on Fe-based catalysts in ozonation process, the heterogeneous catalytic ozonation with Fe-loaded biochar lacks a comprehensive compendium. This review intends to introduce the research progress on Fe-based catalysts and Fe-loaded biochar in heterogeneous catalytic ozonation progress, summarize and further explore the mechanisms and detection techniques of various active components in catalytic ozonation, as well as providing fresh insights for future research. Graphical abstract: Image 1 Highlights: Fe-based catalysts are frequently applied in the ozone-based AOPs. Biochar plays a significant role as the supporter of Fe-based catalysts. The application of Fe-based catalysts in heterogeneous ozonation is complied. The mechanisms of Fe-based catalysts in the ozonation process are reviewed.